2017
DOI: 10.1177/1744806917737461
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal functional integration across core brain networks in migraine without aura

Abstract: BackgroundAs a complex subjective experience, pain processing may be related to functional integration among intrinsic connectivity networks of migraine patients without aura. However, few study focused on the pattern alterations in the intrinsic connectivity networks of migraine patients without aura.ResultsThirty-one migraine patients without aura and 31 age- and education-matched healthy controls participated in this study. After identifying the default mode network, central executive network and salience n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 43 publications
(106 reference statements)
5
35
0
Order By: Relevance
“…The SN plays a critical role in the functional integration between RSNs . FC analysis showed significant increases in FC between the left and right INS in OB compared with NW, contributing to the disruption of FC within the SN.…”
Section: Discussionmentioning
confidence: 97%
“…The SN plays a critical role in the functional integration between RSNs . FC analysis showed significant increases in FC between the left and right INS in OB compared with NW, contributing to the disruption of FC within the SN.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies in episodic migraine concordantly found that DMN is less connected between attacks of migraine without aura [37,38]. Whereas, the intrinsic functional connectivity of the DAS was reduced [39] in episodic migraine interictally and less connected with the DMN [9].…”
Section: Discussionmentioning
confidence: 87%
“…Several studies in episodic migraine concordantly found that DMN is less connected between attacks of migraine without aura [45,46]. Whereas, the intrinsic functional connectivity of the DAS was reduced [47] in episodic migraine interictally and less connected with the DMN [9].…”
Section: Discussionmentioning
confidence: 87%